Growing Green : The Economic Benefits of Climate Action - Deichmann, Uwe; Zhang, Fan (Washington, DC: World Bank, 2013)
Pollution from fossil fuels and degraded natural lands are raising the earth’s temperature. The evidence of the causes of global warming is clear, as are its consequences. The economic impacts of climate change are already apparent and they threaten development gains. Extreme weather events have brought severe droughts to Central Asia, heat waves and forest fires to Russia, and floods to Southeastern Europe. Unchecked emissions will come at rising economic cost and increasing risk to individuals. There is a clear case for all of the world’s economies to move to a low-carbon growth path.